Active and relict contact karst morphological forms of the Slavina corrosional plain - Švara, Astrid; Mihevc, Andrej; Zupan Hajna, Nadja (Acta Carsologica, 2023)
The Slavinski ravnik corrosional plain is a small area of Dinaric karst in Slovenia, located at the contact between impermeable flysch and karstified carbonate rocks, where the most representative ponor contact karst features have formed. Due to erosion, multiphase regional tectonic uplift, and sedimentation, a paragenetic cave system, active and relict blind valleys can be observed, reflecting the different stages of the morphogenesis of this area. To obtain a better overview and detailed understanding of the past and present behaviour of a dynamic karst system, in which hydrology is closely related to the spatial distribution and the extent of contact karst (allogenic) morphological features, geomorphological and sedimentological mapping was conducted. Maps were digitized using ESRI ArcMap and Golden Software Surfer based on DEM and LiDAR imagery. During the survey, the active cave system Markov spodmol and Vodna jama v Lozi, the relict unroofed cave Brezstropa jama v Lozi, Biščevci blind valley, Sajevško polje blind valley, Ivačevci blind valley, and Sajevško polje sediment accumulation were studied, and active and relict karst features were determined. It is concluded that their location, interrelation, sedimentological record, and overall occurrence show different stages of development of these geomorphic features with their hydrological function, indicating different stages of formation of the northern margin of the Slavinski ravnik at least within the last 4 million years. In summary, this is a unique, comprehensive study site where we can observe exposed and preserved elements, that reveal a gradual development of a ponor contact karst area, which in most cases is not well preserved due to erosion and karst denudation processes.